Sufi Women of South Asia: Veiled Friends of God - Aftab, Tahera (Leiden ; Boston : Brill, 2022)
"In Sufi Women of South Asia. Veiled Friends of God, the first biographical compendium of hundred and forty-one women, from the eleventh to the twentieth century, Tahera Aftab fills a serious gap in the existing scholarship regarding the historical presence of women in Islam and brings women to the centre of the expanding literature on Sufism. The book's translated excerpts from the original Farsi and Urdu sources that were never put together create a much-needed English-language source base on Sufism and Muslim women. The book questions the spurious religious and cultural traditions that patronise gender inequalities in Muslim societies and convincingly proves that these pious women were exemplars of Islamic piety who as true spiritual masters avoided its public display"
Keywords: Women sufis -- Biography. -- South Asia; Muslim women -- Biography -- South Asia; Women in Islam -- South Asia